An in situ study of growth of Lemongrass Cymbopogon flexuosus (Nees ex Steud.) W. Watson on varying concentration of Chromium (Cr+6) on soil and its bioaccumulation: Perspectives on phytoremediation potential and phytostabilisation of chromium toxicity. (February 2018) - Patra, Deepak Kumar; Pradhan, Chinmay; Patra, Hemanta Kumar
Abstract: Chromium (Cr) contamination in soil is a growing concern in sustainable agricultural production and food safety. Remediation of Cr from contaminated soils is a challenging task which may not only help in sustaining agriculture but also in minimizing adverse environmental impacts. Pot culture experiments were performed with the application of varied concentration of Cr +6 to assess the Chromium accumulation potential of Lemongrass and to study the impact of toxic concentration of Cr +6 on morphological, physiological and biochemical parameters of the plant. The results showed an increasing accumulation trend of Chromium with increasing Chromium concentrations in both root and shoot of 60 days old Lemongrass plants, while the protein and chlorophyll contents decreased. Similarly, accumulation of Cr increased the levels of proline and antioxidant enzymes indicating the enhanced damage control activity. The potentiality of the plant with the capacity to accumulate and stabilize Cr compound in Cr contaminated soil by phytoremediation process has been explored in the present investigation. Graphical abstract: Image 1 Highlights: The degree of toxicity using varying concentrations of Cr +6 on growing Lemongrass. Phytoaccumulation ability of Lemongrass with reference to tolerance indices. Severity of Chromium toxicity stress on morphological, physiological and biochemical lesions. Chromium bioavailability in plants.